ä¸¹æˆŽå¸ƒæ‹‰å›½ç«‹å¤§å¦å¸ˆèŒƒæ•™è‚²å¦é™¢æ±‰è¯ä¸“ä¸š2014å±Šå¦ç”Ÿ ä½¿ç”¨â€œæ»¡è¶³â€å’Œâ€œæ»¡æ„â€çš„åè¯¯åˆ†æž - Fitrianingsih, Bella; Ina, Ina; Lusi, Lusi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractGrammar is the rules of how to use words. Grammar is also one of the three elements of language. In Chinese, you will learn  parts of speech such as verb, noun, adjective, adverb, preposition, conjunction,etc. Each part of speech has its own usage. Many Chinese words have similar meanings, such as "manzu" and "manyi". In learning process, it often leads to language misuse if students are unable to distinguish between two similiar words. The writer conducted a research on the "manzu" and "manyi" of Chinese students of Teachers Training and Education Faculty year 2014 in Tanjungpura University  to analyze and understand the situation of students using these two words. The writer only investigated two types of errors which are errors and mistakes in the wrong order. The writer concluded that the error rate of "manzu" is 38.38% and 26.67% for "manyi", and the common type of errors is the mistake in words usage. In addition, the writer also  concluded that the reason of the error is because the influence in transferring language from the mother language to the target language. Key words: "Manzu" and "Manyi", Error analysis, Error reason